Effects of Nitrogen and Intercropping on the Occurrence of Wheat Powdery Mildew and Stripe Rust and the Relationship With Crop Yield - Luo, Chaosheng; Ma, Liankun; Zhu, Jinhui; Guo, Zengpeng; Dong, Kun; Dong, Yan (Frontiers in Plant Science, 2021)
Wheat powdery mildew (Blumeria graminis f. sp. tritici) and stripe rust (Puccinia striiformis Westend f. sp.tritici) restrict wheat production in southwest China. Nitrogen fertilizers may influence outbreaks of these wheat diseases where wheat/faba beans are intercropped. To clarify how intercropping and varying nitrogen levels influence wheat powdery mildew and stripe rust and their relationship with crop yield, two consecutive field experiments were conducted from 2015 to 2017. Three cropping regimens (monocropped wheat, monocropped faba beans, and intercropped wheat/faba beans) and four nitrogen levels [N0 (0kg•ha-1), N1 (90kg•ha-1), N2 (180kg•ha-1) and N3 (270kg•ha-1)] were evaluated. In two consecutive planting seasons, the incidence and disease index of powdery mildew and stripe rust increased, while the disease index was more affected by nitrogen levels than their incidence. Both diseases were most prevalent at the N3 level. Compared with monocropping, intercropping (N0~N3 levels) reduced the incidence of powdery mildew by 2.8%~37.0% and disease index by 15.5%~47.4%, increased the relative control effect by 10.7%~56.2% and 16.3%~47.2%, reduced the incidence of stripe rust by 2.9%~42.7% and disease index by 8.3%~42.2%, and increased the relative control effect by 5.9%~43.7% and 8.8%~42.1%. Outcome was most influenced by the N2 level. Intercropping yield increased with increasing nitrogen by 25.0%~46.8%. Overall LER was 1.30-1.39. The correlation coefficient between disease index and wheat yield for both diseases was -0.7429 to -0.9942, a significant negative correlation, most significant at N1. N regulation in intercropped wheat/faba beans can control powdery mildew and stripe rust, and optimize wheat yield. Intercropping at 180kg•ha-1 N2 resulted in the highest yield.